The part-time assistant professor in the Spanish university from an autoethnographic approach - Beatriz Garcia-Ortega; Javier Galan-Cubillo; Juan A. Marin-Garcia (WPOM : Working Papers on Operations Management)
The figure of the part-time assistant professor has been gaining presence in Spanish uni-versities since its inception in the 1980s, especially since 2010 with the economic crisis and the reduction in the replacement rate of university professors. Despite the growing rele-vance within the university faculty, the controversy that the use of this figure has generated, and the problems faced by this group of professors in their performance, there is a shortage of publications focused on questioning its role, how this figure is used and how its perfor-mance can be smoothed and favored. To contribute in this direction, and with the purpose of encouraging better management of this figure from the perspective of human resources and the quality of the service offered, this article addresses the use and improvement of the benefits of the part-time assistant professor in the Spanish university from a collaborative autoethnographic approach. In this sense, a series of aspects are identified and proposed to improve the framework and conditions in which part-time assistant professors carry out their activity, as well as their competences and attributions, in order to promote reflection and debate among teachers, scholars, government bodies and other actors with the ability to influence their performance according to the goals for which this figure was actually conceived, which ultimately would result in greater self-realization and personal satisfac-tion of these professors, and contribute to educational excellence, as well as a better quali-ty of service and superior competitiveness of universities.